A rare case of penile cancer in situ metastasizing to lymph nodes - Kim, Brian; Garcia, Francisco; Touma, Naji; Moussa, Madeleine; Izawa, Jonathan I. (Canadian Urological Association Journal, 2013)
Penile carcinoma in situ, or Queyrat’s erythroplasia, is a rare condition of the glans penis. This lesion has been associated with invasive squamous cell carcinoma; however, metastasis without an invasive component is extremely rare. There have only been 2 documented cases with metachronous metastases. We report a third case in which metastases were diagnosed at presentation. The patient was a 51-year-old man who presented with a glans penile lesion and bilateral inguinal masses later determined to be carcinoma in situ with metastases to the inguinal and pelvic lymph nodes. He subsequently underwent a partial penectomy and lymphadenectomy followed by adjuvant chemotherapy and radiation. This case is discussed, along with a brief review of the literature.